A measurement of the configuration of a building enterprise management structure/Statybos įmonės valdymo struktūros konfigūracijos matavimas - Romualdas Ginevičius (Journal of Civil Engineering and Management, 1996)
The configuration of a building enterprise management structure represents the outer form of a management system and is determined by two main principles of organizational formation, namely by specialization and coordination. The configuration may be measured by an organigram of an enterprise, i.e. by a graphical figure of a management system.